1993
DOI: 10.1007/bf03011315
|View full text |Cite
|
Sign up to set email alerts
|

In vitro determination of human dura mater permeability to opioids and local anaesthetics

Abstract: In vitro determination of human dura mater permeability to opioids and local anaesthetics Identification of specific opiate receptors in the brain and spinal cord and the subsequent demonstration that spinal (epidural and intrathecal) administration of opiates may lead to segmental spinal analgesia is the basis for epidural narcotic injection, i-3 Studies in animals and humans have demonstrated recently that pre-and postsynaptic receptors in the substantia gelatinosa of the dorsal horn of the spinal cord may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 15 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Similar drug administrations are also frequently used for lower abdominal, urogenital, rectal, and lower extremity surgery (Morgan et al, 2006). These treatments are based on the in vitro–verified passage of local anesthetics and narcotics through the spinal meninges (McEllistrem and Bennington, 1993; Grouls et al, 2000). Spinal intrathecal baclofen therapy is also acknowledged to be effective in the relief of spasticity and pain associated with cerebral palsy, sclerosis multiplex, and other neurologic disorders (Guillaume et al, 2005; Ben Smail et al, 2006).…”
mentioning
confidence: 99%
“…Similar drug administrations are also frequently used for lower abdominal, urogenital, rectal, and lower extremity surgery (Morgan et al, 2006). These treatments are based on the in vitro–verified passage of local anesthetics and narcotics through the spinal meninges (McEllistrem and Bennington, 1993; Grouls et al, 2000). Spinal intrathecal baclofen therapy is also acknowledged to be effective in the relief of spasticity and pain associated with cerebral palsy, sclerosis multiplex, and other neurologic disorders (Guillaume et al, 2005; Ben Smail et al, 2006).…”
mentioning
confidence: 99%
“…In the present study, laminectomy-induced cauda equina adhesion was also enhanced by kaolin. It is speculated that an increased severity of the epidural inflammation may affect the cauda equina because some inflammatory substances may pass through the dura mater [17] or may perfuse through the rapid transport route between the epidural space and the intraneural capillaries of the nerve roots [4]. Moreover, in the previous study, when cauda equina adhesion occurred in the kaolin group, nerve degeneration was observed in three of five rats at 1 week after surgery [33].…”
Section: Discussionmentioning
confidence: 93%
“…9 Pearce and Grimmer 10 reported that the amount of elastin in tissues decreases with age and that reduced elastin content significantly affects biomechanical strength. McEllistrem et al 11 reported that agerelated structural changes to the dura mater may account for the increased dural permeability. Hence, degenerative changes to the dura mater may induce weakening or increased permeability.…”
Section: Discussionmentioning
confidence: 99%